2010
DOI: 10.1111/j.1365-2052.2009.01984.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of polymorphisms in the ovine Shadow of prion protein (SPRN) gene and assessment of their effect on promoter activity and susceptibility for classical scrapie

Abstract: Shadow of prion protein (SPRN) is an interesting candidate gene thought to be involved in prion pathogenesis. In humans, an association has already been discovered between mutations in SPRN and the incidence of variant and sporadic Creutzfeldt-Jakob disease. However, in sheep, the effect of mutations in SPRN is largely unknown. Therefore, we analysed the presence of mutations in the entire ovine SPRN gene, their association with scrapie susceptibility and their effect on SPRN promoter activity. In total, 26 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 45 publications
(43 reference statements)
1
21
0
Order By: Relevance
“…Using the Promoter Scan program, the forward strand spanning g.1176 to g.1426 was predicted as the putative promoter region for both the cattle and buffalo sequences. Conversely, Lampo et al had suggested the ovine SPRN promoter to be located in a more 5′ distant region, spanning g.739–1259 [26] (similar to bovine SPRN g.845–1407). Based upon this information, we first constructed the pGL3Basic reporter plasmid containing the fragment g.808–1691 to cover both possibilities.…”
Section: Resultsmentioning
confidence: 99%
“…Using the Promoter Scan program, the forward strand spanning g.1176 to g.1426 was predicted as the putative promoter region for both the cattle and buffalo sequences. Conversely, Lampo et al had suggested the ovine SPRN promoter to be located in a more 5′ distant region, spanning g.739–1259 [26] (similar to bovine SPRN g.845–1407). Based upon this information, we first constructed the pGL3Basic reporter plasmid containing the fragment g.808–1691 to cover both possibilities.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, frame shift mutations induced by a single base pair insertion at codon 46 of the SPRN gene were found in two variant CJD patients 20 . In sheep, two alanine-deletion polymorphisms located in the hydrophobic region of the Sho protein showed significantly different genetic distributions between scrapie-affected animals and healthy animal 24 . In goats, an indel polymorphism (602_606insCTCCC) in the 3′ untranslated region (UTR) was related to scrapie susceptibility 20 .…”
Section: Introductionmentioning
confidence: 97%
“…In humans, the null allele of the SPRN gene showed association with variant CJD 25 . In sheep, a polymorphism causing a deletion of two alanines was related to the susceptibility for scrapie 26 . In goats, an insertion/deletion polymorphism located on the 3′ UTR was associated with the susceptibility for scrapie 27 .…”
Section: Introductionmentioning
confidence: 99%